NEW APPROACHES TO VISUAL DESIGN: THE ROLE OF AI-BASED CHATBOT AND GENERATIVE TOOLS - Kaya, Abdulselam; Kavuran, Tamer (Anadolu Univ, 2025)
Artificial intelligence technologies, which are increasingly taking place in the world of art and design, are reshaping the dynamics of these fields by leading to radical changes in creative processes and disciplinary practices. In particular, chatbots and generative AI tools accelerate the creation process and bring along various discussions in the context of creativity, originality and ethical issues. In this context, the study aims to discuss the role of AI in design processes from a holistic perspective by using the compilation method. In the study, firstly, the role of AI in the field of design is examined in general terms, and then different types of commands (simple, detailed, abstract and technical) are emphasized. In this direction, the study points out that AI tools produce consistent outputs in simple commands and varied outputs in detailed and abstract commands due to algorithmic limitations; although successful in technical commands, it leads to ethical and legal debates in terms of originality and copyright. In the rest of the study, the effects of AI tools on design processes are examined with their advantages and disadvantages; concepts such as creativity, speed, efficiency, accessibility, originality, copyright and property are evaluated and suggestions for the future are presented. In conclusion, while AI has become an important actor in design processes, more research is needed on creative originality, ethical boundaries, and their long-term impact. Interdisciplinary work is critical to consciously and sustainably navigate the role of AI in art and design.
Keywords: Artificial intelligence; Design; Chatbot; GenAI